Sex differences in the patterns of police contact during childhood and adolescence: A population-based study of 79,446 Australian young people - Whitten, Tyson (Journal of criminology, 2025)
This study provides the first Australian epidemiological evidence of sex differences in patterns of contact with police during childhood and adolescence. Using population-based data for 79,446 young people in the New South Wales Child Development Study, we report that one-in-four had contact with police by their 17th birthday. Boys were generally more likely than girls to have contact with police, especially as a person of interest, while girls were more likely to have contact as a victim of sexual assault and of harassment. However, prior to the age of 10 years, the rate of police contact was higher for girls, whereas from age 10 through 16 years, the rate of contact was greater for boys. Consideration of the location of incidents did not significantly affect the general pattern of higher rates of police contact in boys, although girls were more likely to have police contact as a victim or witness in educational facilities and in residential premises. Overall, this research demonstrates that young people's contact with police is common, suggesting that law enforcement might adopt a sex-specific and trauma-informed response in their interactions with young people.